The Influence of Service Quality on BPJS Inpatients’ Satisfaction at Raden Mattaher Hospital: A Cross-Sectional Study - Nurwan Alkahfi; Dwi Noerjoedianto; Andi Subandi; Willia Novita Eka Rini; Muldiasman Muldiasman; Asparian Asparian (Rifa'Institute, 2026)
Introduction: Service quality is a key determinant of patient satisfaction in hospital settings, particularly for National Health Insurance (BPJS) participants. Raden Mattaher Hospital Jambi, as a referral hospital, experiences increasing BPJS inpatient visits. However, complaints and fluctuations in satisfaction index indicate potential service quality gaps. This study aimed to analyze the influence of service quality dimensions on BPJS inpatient satisfaction. Objective: This study aimed to analyze the influence of service quality dimensions on BPJS inpatient satisfaction. Method: This quantitative study used a cross-sectional design conducted in the inpatient wards of Raden Mattaher Hospital in 2025. A total of 424 BPJS inpatients were selected using purposive sampling. Data were collected using a SERVQUAL-based Likert questionnaire covering tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed using univariate, bivariate (simple linear regression), and multivariate (multiple linear regression) analysis with SPSS at α=0.05. Result and Discussion: Most respondents rated service quality as good (58.3%). The mean satisfaction score was 79.10±12.71. Partially, reliability (p=0.048) and assurance (p=0.000) significantly influenced satisfaction, while tangibles (p=0.312), responsiveness (p=0.087), and empathy (p=0.421) were not significant. Simultaneously, all dimensions significantly affected satisfaction (p=0.000) with R²=0.106. Assurance was the dominant factor (β=1.238). Conclusions: Service quality significantly influences BPJS inpatient satisfaction, with assurance as the strongest determinant. Strengthening professional competence and patient trust is essential to improve satisfaction levels.